Multimodal system designed to reduce errors in recording and administration of drugs in anaesthesia: prospective randomised clinical evaluation. (22nd September 2011) - Merry, Alan F; Webster, Craig S; Hannam, Jacqueline; Mitchell, Simon J; Henderson, Robert; Reid, Papaarangi; Edwards, Kylie-Ellen; Jardim, Anisoara; Pak, Nick; Cooper, Jeremy; Hopley, Lara; Frampton, Chris; et al.
Abstract : Objective To clinically evaluate a new patented multimodal system (SAFERSleep) designed to reduce errors in the recording and administration of drugs in anaesthesia. Design Prospective randomised open label clinical trial. Setting Five designated operating theatres in a major tertiary referral hospital. Participants Eighty nine consenting anaesthetists managing 1075 cases in which there were 10 764 drug administrations. Intervention Use of the new system (which includes customised drug trays and purpose designed drug trolley drawers to promote a well organised anaesthetic workspace and aseptic technique; pre-filled syringes for commonly used anaesthetic drugs; large legible colour coded drug labels; a barcode reader linked to a computer, speakers, and touch screen to provide automatic auditory and visual verification of selected drugs immediately before each administration; automatic compilation of an anaesthetic record; an on-screen and audible warning if an antibiotic has not been administered within 15 minutes of the start of anaesthesia; and certain procedural rules—notably, scanning the label before each drug administration) versus conventional practice in drug administration with a manually compiled anaesthetic record. Main outcome measures Primary: composite of errors in the recording and administration of intravenous drugs detected by direct observation and by detailed reconciliation of the contents of used drug vials against recorded administrations; and lapses in responding to an intermittent visual stimulus (vigilance latency task). Secondary: outcomes in patients; analyses of anaesthetists' tasks and assessments of workload; evaluation of the legibility of anaesthetic records; evaluation of compliance with the procedural rules of the new system; and questionnaire based ratings of the respective systems by participants. Results The overall mean rate of drug errors per 100 administrations was 9.1 (95% confidence interval 6.9 to 11.4) with the new system (one in 11 administrations) and 11.6 (9.3 to 13.9) with conventional methods (one in nine administrations) (P=0.045 for difference). Most were recording errors, and, though fewer drug administration errors occurred with the new system, the comparison with conventional methods did not reach significance. Rates of errors in drug administration were lower when anaesthetists consistently applied two key principles of the new system (scanning the drug barcode before administering each drug and keeping the voice prompt active) than when they did not: mean 6.0 (3.1 to 8.8) errors per 100 administrations v 9.7 (8.4 to 11.1) respectively (P=0.004). Lapses in the vigilance latency task occurred in 12% (58/471) of cases with the new system and 9% (40/473) with conventional methods (P=0.052). The records generated by the new system were more legible, and anaesthetists preferred the new system, particularly in relation to long, complex, and emergency cases. There were no differences between new and conventional systems in respect of outcomes in patients or anaesthetists' workload. Conclusions The new system was associated with a reduction in errors in the recording and administration of drugs in anaesthesia, attributable mainly to a reduction in recording errors. Automatic compilation of the anaesthetic record increased legibility but also increased lapses in a vigilance latency task and decreased time spent watching monitors. Trial registration Australian New Zealand Clinical Trials Registry No 12608000068369.